(untitled) (CIPEEX, 2025)
The indiscriminate use of pesticides has increased dermatological, respiratory, neurological, reproductive, psychiatric, and developmental problems. Despite this, Brazil is still the country that uses the most pesticides in the world. The objective of this study is to identify the number of pesticide poisonings in the municipalities that make up the Northeast I and Northeast II health regions and the cases of neurological problems in these locations in the period 2010-2022. This is an exploratory and descriptive study that used data from SINAN and the Goiás State Health Secretariat, considering cases of poisoning by municipality, type of exposure, circumstances of exposure, and evolution, as well as the active ingredient involved in occupational poisoning. In addition, the number of hospitalizations and deaths from neurological disorders was identified. It was found that the highest number of agricultural pesticide poisonings was in the Northeast II region, compared to the Northeast I region. Most exposures were single, acute episodes, involving habitual exposure, which evolved to cure without sequelae. Neurological disorders maintain the characteristic pattern of poisoning by region. Therefore, this study is of paramount importance to the scientific community, as there is a need for more information on the consumption of agricultural pesticides and their impacts, both for farmers and the local community.